Limiting factors for yields of field tomatoes grown by smallholders in tropical regions - Huat, J.; Doré, T.; Aubry, C. (Elsevier, 2013)
Tomatoes are widely cultivated in developing countries and are a major source of income for small-scale farmers. Yields of field-grown tomatoes vary considerably under tropical conditions but the main factors that limit yields remain to be identified. To this end, we conducted an on-farm survey in 22 fields in 2003 and in 28 fields in 2005 in a range of socio-economic settings typical of smallholder farms on the island of Mayotte (Indian Ocean). Data on crop management, fulfilment of water requirements, weed density, nitrogen absorption by the crop and nutrient availability in the soil, as well as the sanitary status of the crop were recorded at two-week intervals throughout the crop cycle. The data were analysed by principal component analysis, and multiple linear regression. Yields varied between years and sites from 0.7 to 45.3 t ha−1 in 2003 and from 8.1 to 89.1 t ha−1 in 2005. In 2003, the number of fruits per m2, fruit weight, the health status of the crop, and the cation exchange capacity of the soil explained 84.7% of yield variability among fields. In 2005, the number of fruits per m2 and the health status of the crop explained 84% of yield variability. In 2003, 61.8% of the variability of the number of fruits per m2 was explained by health status and the number of plants per m2, whereas in 2005, 65.6% of the variability was explained by health status, the number of pesticide applications, and planting density. The results of this study indicate that tomato yield could be increased by improving the health status of the crop by improving the efficiency of crop protection practices and by increasing planting density.